The Domesticated Penis : How Womanhood Has Shaped Manhood - Cormier, Loretta A. (Book collections on Project MUSE., 2015)
"The Domesticated Penis is the first anthropological history of the penis, incorporating evidence from evolutionary theory, primatology, archaeology, and cultural anthropology"--